Ecophilosophical and Ecopsychological Aspects of Sustainable Consumption and Lifestyle - Niedek, Mikołaj (Studia Ecologiae et Bioethicae, 2022)
The aim of the article is to outline the philosophical and psychological dimensions of a sustainable lifestyle based on responsible consumption. In the author’s opinion, moderate consumption and an ecologically balanced way of living should, for their durability, have a broader mental and worldview background. The article will present and compare the concepts of the eco-philosophy of Henryk Skolimowski and the ecopsychology of Theodore Roszak in terms of cognitive, ideological, and axiological propositions of these concepts that can form the motivating basis for responsible living on Earth. In the author’s opinion, apart from the economic dimension, the adoption of ecological ethics and of ecological sensitivity is crucial for the permanent rooting of sustainable consumption patterns in people's attitudes. Ecophilosophical and ecopsychological concepts can significantly help in this, contributing to human sensitivity to environmental issues related to the contemporary ecological crisis. The ecophilosophical and ecopsychological approach, in the author’s opinion, need each other because they use complementary perspectives and methods of building ecological awareness. In the process of environmental education and shaping sustainable life attitudes, they are equally necessary for the effectiveness of achieving the goals of education for sustainable development and promoting an environmentally responsible lifestyle in society.